Odpowiedzi

2009-12-06T21:44:30+01:00
a)a2=5/12;
a3=2/15

q = a₃: a₂ = 2/15 :5/12 = 2/15*12/5= 8/25
q = 8/25
a₂ = a₁*q = 5/12
a₂ = a₁*(8/25) = 2/15
a₁ = 2/15*25/8 = 5/12
an = a₁*q do potegi (n -1)
an = (5/12)*(8/25) do potegi (n-1)


b)a2=7;
a4=28

a₂ = a₁*q = 7
a₄ = a₁*q³ = 38

a₁= 7:q
7:q *q³ = 28

a₁= 7:q
7*q² = 28

a₁= 7:q
q² = 28 :7

a₁= 7:q
q = ± √4 = ±2

a₁ = 7 : (-2) lub a₁ = 7 :2
q = -2 q = 2

a₁= -7/2 lub a₁ = 7/2
q = -2 q = 2

an = (-7/2)*(-2) do potęgi(n-1) lub an = (7/2)*2 do potegi (n-1)
2 3 2